ANALISIS LAIK FUNGSI JALAN NASIONAL BATAS KOTA SIGLI – BEUREUNUEN MENGGUNAKAN METODE ANALYTIC HIERARCHY PROCESS - Teuku Zulhadi; Sofyan M. Saleh; Renni Anggraini (JURNAL TEKNIK SIPIL, 2017)
Abstract: Road operated for the public must be feasible of a function where the condition of the road meet the technical requirement feasibility to provide road infrastructure which is safe and convenient for its users, as well as to reduce serious injuries and fatalities. Sigli border-Beureunuen road is an eastern national road of Aceh province that connects the town of Sigli (the capital of Pidie district/ central regional government) with Beureunuen town (Commerce City). This road is also the Sumatra highway that serves as the main axis connecting people’s activities and heavy traffic road with the high level of accidents. The purpose of this study was to determine the perception of the respondents (the organizers of the road, traffic providers, and transport providers) about the importance of function feasibility and to know about the technical requirements of function feasibility that is fulfilled or prioritized. This study used Analytic Hierarchy Process (AHP), the assessment system to include the alternative technical requirements of function feasibility and safe, convenient, and economical chosen criteria based on the data processing from a questionnaire survey. The number of the respondents in this study was 9 (nine) people, who had the qualifications and competence in terms of the road function feasibility. The results from the study showed that the main factor in determining the road function feasibility was the Safety road conditions (43.90%). Whereas according to the respondents, the technical requirements that were prioritized on the national road of Sigli border-Beureunuen was management and traffic engineering (signs and markings) (34.81%).Abstrak: Suatu ruas jalan dinyatakan laik fungsi apabila kondisi ruas jalan tersebut telah memenuhi persyaratan teknis kelaikan untuk memberikan infrastruktur jalan yang aman, nyaman dan berkeselamatan bagi penggunanya, juga untuk mengurangi luka berat dan kematian akibat kecelakaan. Ruas jalan Batas Kota Sigli - Beureunuen merupakan jalan lintas timur Sumatera di Provinsi Aceh yang berfungsi sebagai poros utama menghubungkan antar pusat kegiatan dan mempunyai tingkat kepadatan lalu lintas yang tinggi serta tingkat kecelakaan yang terjadi juga tinggi. Penelitian ini bertujuan untuk mengetahui persepsi responden (penyelengara jalan, penyelenggara lalu lintas dan penyelenggara angkutan) tentang pentingnya laik fungsi jalan dan untuk mengetahui tentang bagian persyaratan teknis kelaikan fungsi jalan yang paling utama dipenuhi atau diprioritaskan. Penelitian ini menggunakan metode survei kuesioner, data diolah dan dianalisis dengan menggunakan metode Analityc Hierarchy Process (AHP) yang merupakan sistem dalam penilaian dengan menyertakan alternatif persyaratan teknis kelaikan jalan dan kriteria terpilih aman, nyaman, berkeselamatan serta ekonomis. Responden pada penelitian ini berjumlah 9 (sembilan) orang, yang memiliki kualifikasi dan kompetensi dalam hal uji laik fungsi jalan. Hasil dari penelitian menunjukkan bahwa faktor utama dalam penentuan laik fungsi jalan adalah kondisi jalan yang berkeselamatan (43,90%). Sedangkan syarat teknis laik fungsi jalan pilihan responden yang paling utama dipenuhi atau diprioritaskan untuk diterapkan pada ruas jalan Batas Kota Sigli – Beureunuen adalah manajemen dan rekayasa lalu lintas (rambu dan marka) (34,81%).